INFORMATION SYSTEM DESIGN OF VILLAGE-OWNED ENTERPRISES IN PEKON SINAR PETIR, BASED ON WEB AS A PROMOTIONONAL MEDIA FOR VILLAGE SUPERIOR PRODUCTS - Sri Ipnuwati; Sri Surya Mandala; Dimas Irianto Ardi (IJISCS (International Journal of Information System and Computer Science), 2023)
The development of this era in the field of information technology is very fast. This phenomenon will certainly change and become a tool for business competition between companies and organizations. A village-owned enterprise is a business entity formed based on Law No. 6 of 2014 concerning villages. With the formation of village-owned enterprises, it is hoped that villages will become independent and be able to improve the economic level of the community. In this case, the village-owned enterprise "Karya Abadi" in Pekon Sinar Petir, Talang Padang District, Tanggamus Regency, Lampung Province, has been formed since 2016 and only started in 2021. This village-owned enterprise is engaged in the following business sectors: animal husbandry, agriculture, plantations, financial services, equipment and supplies, waste management, and savings and loans. Until now, the business entity has not had a website to promote products or facilitate the dissemination of information. This research was conducted to solve this problem. This research is in the form of a website framework design for village-owned enterprise "Karya Abadi", which in the future will build a website-based information system. This research was conducted using the waterfall method, which will make it easier to develop and build an information system for the village-owned enterprise